Digital Lusternik-Schnirelmann category - Borat, Ayşe; Vergili, Tane (Scientific Technical Research Council Turkey-Tubitak, 2018)
In this paper, we define the digital Lusternik-Schnirelmann category cat(kappa), introduce some of its properties, and discuss how the adjacency relation affects the digital Lusternik-Schnirelmann category.
Keywords: Lusternik-Schnirelmann category; digital topology